Optimal Scheduling Policy for a Multi-upgraded Software System under Fuzzy Environment - Adarsh Anand; Subhrata Das; Mohini Agarwal; V.S.S. Yadavalli (Institute for Research and Community Services (LPPM) ITB, 2019)
Many reliability growth models related to the concept of multi-upgrading have recently been proposed. This concept has helped software developers to develop a competitive edge over competitors by regularly introducing their software upgrades in the market at the optimal moment. The software reliability literature offers many different release-time policies, both under crisp and fuzzy environment. This paper presents a generic model of a multi-upgraded software system. The optimal scheduling policy for software under a fuzzy environment was determined. The proposed model was examined on a real-life failure data set of four software releases. The results obtained are encouraging.